A post-mortem on the Malaysian content-based instruction initiative - Lee, Seung Chun (J. Benjamins Pub. Co., 2014)
This is a post-mortem on Malaysian TeSME (Teaching of Science and Mathematics in English) program based on its comparison with Canadian immersion programs. Malaysia and Canada have some common sociological aspects such as the size of population, the ratio of indigenous people and immigrants, and multilingual contexts. It also has in common various core elements in the set of criteria proposed by Swain and Johnson (1997) to define a prototypical immersion program. Thus, the lessons Canadians have learned from immersion may be seen as significant guiding light for TeSME and other attempts of content-based instruction programs. Canadian immersion has been different from TeSME at least in terms of three core features: overt support exists for the L1; the teachers are bilingual; and the classroom culture is that of the local L1 community. These differences made four issues more prominent: Learning outcome of TeSME; mainstay of TeSME; judicious use of L1; and function of TeSME. Finally some suggestions are proposed: give higher priority to promoting concept development across languages for now; make English classes more effective; promote bilingualism in TeSME; and extend TeSME’s function to understanding and integrating other cultures and languages.